The last morning star : talks on the enlightened woman mystic, Daya - Osho. (Ahmedabad : Jaico Publishing House, 2019)
Talks on the enlightened woman mystic, Daya. The last morning star symbolizes all that is ephemeral in the world. Talking on the playful and provocative poetry of Daya, Osho takes us on a journey from the transient, outer world to the eternal, boundless world within. This is a journey of the heart -the joyous, spontaneous and at times uncompromising way of an enlightened woman mystic. "If someone clings to the last morning star, how long will their happiness last? It is like catching a bubble of water. The bubble will burst before you can even hold it. You can try in thousands of ways to make it stay, but it will not stay and this is what we are always doing -the whole world does it. What are the things that we try to hold on to? Relationships, attachments, love, our husband or wife, sons and daughters, wealth and riches, fame, position, prestige
Keywords: Spiritual life; Self-realization.